INTERACTIONS OF WARFARIN - Řehulková, Olga (Biomedical papers, 2001)
In this article, the author reviews and updates the basis of interactions with warfarin, illustrated with appropriateexamples. The interactions with drugs, medicinal herbs and foods are summarised.
Keywords: Drug interactions / Warfarin / Oral anticoagulants / Anticoagulant treatment